1996
DOI: 10.1017/s0022377800019486
|View full text |Cite
|
Sign up to set email alerts
|

Coherent drift-wave structures in toroidal plasmas

Abstract: Using the ion-temperature-gradient-driven drift waves as a paradigm for drift-wave anomalous transport, we explore the structure of the linear and nonlinear modes. Two phases of transport are shown to exist: (i) Bohm-like transport for parameters close to marginal stability; (ii) gyro-Bohm transport for turbulent convection cells in systems driven away from marginal stability. Nonlinear relaxation to large-scale coherent convective structures is observed in three-dimensional toroidal particle simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
1

Year Published

1998
1998
2003
2003

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
2
3
1
Order By: Relevance
“…Some kinetic simulations show also that the ITG-driven mode is often close to the linear stability boundary for measured tokamak parameters (Rewoldt et al 1987). These results agree with the profile consistency principle that was proposed by Coppi (1980), and supported later by Terry et al (1988) and Kishimoto et al (1996). One of the approaches to anomalous transport is that the increased transport will bring the density n (r) and temperature T (r) profiles in tokamak plasmas to marginal stability of strong reactive unstable modes such as the ITGdriven modes.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Some kinetic simulations show also that the ITG-driven mode is often close to the linear stability boundary for measured tokamak parameters (Rewoldt et al 1987). These results agree with the profile consistency principle that was proposed by Coppi (1980), and supported later by Terry et al (1988) and Kishimoto et al (1996). One of the approaches to anomalous transport is that the increased transport will bring the density n (r) and temperature T (r) profiles in tokamak plasmas to marginal stability of strong reactive unstable modes such as the ITGdriven modes.…”
Section: Introductionsupporting
confidence: 89%
“…The formation of coherent long-lived large-scale structures of drift modes is sometimes considered to be one of the main reason for L-H transition to the regime of improved confinement in tokamaks (Ottaviani et al 1990) and sometimes as the reason for anomalous transport (Horton et al 1990;. Although the connection between anomalous transport and coherent structures is still unclear, recent experiments indicate that the correlation length that determines the local transport is determined by nonlinear effects (Weiland 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Although when the ECEI system is measuring in the high field side, the magnetic field on axis is smaller, this change in magnetic field alone cannot explain the observed in-out asymmetry. This also differs from theoretical models of the ion temperature gradient drift instability, which predict that the modes are stronger on the low field side due to bad magnetic field curvature [9], [10]. One possible explanation for this contradiction is that the shearing rate is smaller on the high field side [10].…”
contrasting
confidence: 68%
“…These provide evidence that the observed broadband fluctuations in RTP are related to the toroidal ion temperature gradient drift instability ( mode) [3]. From computer simulations of the mode, it is observed that small-scale drift vortices can coalesce to form large-scale, long-lived coherent structures [9], which are similar to the structures shown in Fig. 2(b).…”
supporting
confidence: 56%
“…It is seen that turbulence is not uniformly distributed over the plasma cross-section. Instead, prominent peaks are seen in the plasma confinement region, which may be related to the coherent structures predicted by theory 34,35 . Of particular interest are the peaks of both MHD and turbulence in the tokamak midplane, outside the q = 2 radius, in both the high and low field side 24,25,35 .…”
Section: Electron Cyclotron Emission Imaging (Ecei)mentioning
confidence: 65%